El fomento a la educación básica en el Distrito del Sur en tiempos de la República de la Gran Colombia (Estudios) - Pita Pico, Roger (2017)
This article examines the progress and setbacks experienced when public schooling spread in Ecuador at the time of the Republic of Gran Colombia. This educational initiative was developed during a transition phase characterized by the clash between the mindset of the old Spanish regime and that of the new Republican system, the latter tending toward lay and inclusive education. After the Wars of Independence and in view of widespread economic recession and fiscal deficits, public schools benefited from private funding. Ultimately, this educational initiative was a favorable opportunity to disseminate the idea of progress and liberal principles, consolidate the political system’s legitimacy, and extol the benefits of the Nation.